Esclavos y la imagen de la justicia paternalista del rey y del virrey en el Veracruz colonial - Magdalena Díaz Hernández (Nuevo mundo - Mundos Nuevos, 2015)
This paper addresses the need of a profound analysis about relation between the slaves and the protective laws and justice of the Viceroy and King, who should apply their paternalistic obligation. This kind of justice, which identified slaves as miserable, was more clearly manifest in Veracruz at the end of the 18th century. It should be noted that the Law of Partidas considered slaves as subject of the king before the Court; this allowed them go through the relationship of domination and justice of their masters in the Indies. For that reason, the runaway slaves appealed in the Mexican Court the protection of the Viceroy and the King as “fathers of minor”. Therefore, the protective system of justice wasn’t exclusive to Indians, but rather it formed part of the colonial juridical culture, to which was added the Code of 1789.